The interimperial and Panamerican origins of the dollar system - Nic Johnson (Duke University, Center for the History of Political Economy (CHOPE), 2024)
The Federal Reserve is commonly depicted as an institution set up by domestic actors to fulfill domestic functions that only later took on international and geopolitical dimensions. Yet we have long had an abundant literature on the financial projection of US power ("Dollar Diplomacy") in which the main characters overlap conspicuously with the cast of domestic, Progressive Era reformers ("corporate liberalism"). Stitching these two stories together with the threads of intellectual history and the theory of monetary hierarchy woven from a new reading of the archives, I show how central banks were always embedded within the violence of the world-system, and how globalization built the nation-state as much as the reverse. After an intensive study of European monetary history, a cohort of corporate intellectuals decided America needed a central bank to keep up with the evolving financial architecture of the late 19th century. Even as their reform efforts were blocked at home, the Spanish-American war opened up new opportunities in the periphery of America's empire. They spent the following decade and a half experimenting, founding new monetary authorities, and studying the great colonial monetary systems of Eurasia. What they discovered was a world of gold exchange standards: proto-Bretton Woods systems in which the metropole was hub and the colonies were spokes. Further opportunities for learning and experimentation arrived with the Roosevelt corollary, when the US claimed the role of international policeman in Latin America. The Monroe Doctrine would be easier to enforce, Teddy figured, if Latin Americans were financially integrated with New York rather than London, Paris, or Berlin; for US security purposes, the Caribbean had to dollarize. Dollar diplomacy met with only limited success, however, because Latin American elites weren't eager to play along. North American money markets weren't liquid or stable enough to anchor the U.S.'s own system, much less anyone else's. At that point the intellectuals came home, having acquired a wealth of experience in monetary reform and management abroad. They argued that successful hegemony in the Americas required going beyond coercion to building the institutions necessary for eliciting consent from foreign elites. They led the Aldrich commission's domestic political campaigns on behalf of US central banking that, after a few twists and turns and the Democratic takeover of 1912, ultimately culminated in the Fed and the birth of the global dollar system.
Keywords: 330